2002
DOI: 10.1159/000067165
|View full text |Cite
|
Sign up to set email alerts
|

Adnexal Torsion during Pregnancy – Management and Literature Overview

Abstract: We present a patient in the 30th week of gestation with adnexal torsion, which was treated by laparotomy with oophorectomy. After 2 days, we had to perform a cesarean section because of bowel obstruction. We discuss the diagnosis and treatment of adnexal torsion in pregnancy and compare laparoscopic management with laparotomy. By reviewing the literature, we evaluate the conservative therapy by detorsion employing Doppler sonography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
1
1
0
1
Order By: Relevance
“…As reported by others, we also found that while AT can occur at any gestational age [10], it is more commonly encountered in the 1 st trimester or in the early weeks of the second trimester [11], which may be at least partially accounted for by the higher rate of functional cysts at the early stages of pregnancy. As shown in univariate analysis in the current cohort, ART was previously found e101 to be a significant risk factor for AT [9].…”
Section: Discussionsupporting
confidence: 86%
“…As reported by others, we also found that while AT can occur at any gestational age [10], it is more commonly encountered in the 1 st trimester or in the early weeks of the second trimester [11], which may be at least partially accounted for by the higher rate of functional cysts at the early stages of pregnancy. As shown in univariate analysis in the current cohort, ART was previously found e101 to be a significant risk factor for AT [9].…”
Section: Discussionsupporting
confidence: 86%
“…The characteristics and clinical findings of ovarian torsion in pregnancy have been mostly reported previously in isolated case reports and small case series (3)(4)(5)(6), and there appears to be limited information on the subject. The diagnosis of ovarian torsion in pregnancy may be a challenging one, because palpation of the ovaries and ultrasound imaging of the ovaries are more difficult than in nonpregnant patients.…”
mentioning
confidence: 99%
“…Surgery should only be started after preparations for an emergency cesarean section. [9]. Auch ein Fall aus Indien zeigt, dass die Adnextorsion in der fortgeschrittenen Schwangerschaft zunächst als Appendizitis fehlinterpretiert werden kann: eine 28-jährige Zweitgravida war in der 23.…”
unclassified